ZETA Converter as a Voltage Stabilizer with Fuzzy Logic Controller Method in The Pico Hydro Power Plant - Anggara Trisna Nugraha; Rachma Prilian Eviningsih (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
The development of the use of renewable energy that is environmentally friendly has been widely carried out, one of which is the use of energy as a turbine drive in the Pico Hydro Power Plant. The main problem in using energy, especially water energy, is the flow of water which can affect the flow of water used to rotate the turbine, so that the voltage on the DC link cannot be kept constant. Therefore, in this paper, we will design and simulate the charging process for a lead acid battery with a DC-DC converter and a Pico Hydro Power Plant as the main source. The type of generator used in the Pico Hydro Power Plant is a DC generator. The output voltage of the DC generator is still fluctuating, so to keep the output voltage constant, a DC-DC converter is needed, namely the ZETA Converter, so that its efficiency will be better when compared to using other types of converters. The ZETA converter with a DC generator as a source will be used for the battery charging process using the Fuzzy Logic Controller so that the output voltage of the ZETA converter can be kept stable or constant. The results obtained in the close loop simulation test are that the output voltage is constant at 14.4 V and the output current is 6.64 A so that it can be used for the battery charging process that will be used for household lighting.